Aprendizado da violência e cultura de resistência: memórias do tráfico atlântico de africanos (séculos XVIII e XIX) - Oliveira, Rafael Domingos (2022)
The paper analyzes four autobiographies that report the experiences of Africans in the Atlantic slave trade networks, between the end of the 18th century and the first half of the 19th century. Mahommah Gardo Baquaqua, Quobna Ottobah Cugoano, Olaudah Equiano and Ukawsaw Gronniosaw were born in different regions of West Africa, were captured, sold as children, crossed long journeys inland to the main ports of embarkation of people and goods and crossed the Atlantic on tumbeiro ships, heading for the Americas. Through their memories, it is possible to understand the roles assumed by the varied range of trafficking agents (African elites, traders, intermediaries, etc.); the conditions of travel on tumbeiro ships, as well as the training and daily life of crews and sea workers; and the socio-cultural aspects of trafficking, such as languages and patterns of resistance, among which are revolts on the high seas.